Avaliação do efeito protetor da Baccharis trimera (Less) DC. (Asteraceae) sobre o dano hepático induzido por tetracloreto de carbono em ratos - Bonilha, Iuri de França (2017)
The objective of this study was to evaluate the effect of Baccharis trimera hydroethanolic crude extract (BtHE), popularly known as carqueja, on CCl4 induced hepatic injury in Wistar rats. The liver is the main organ of metabolism and excretion of the human body, and is continually exposed to xenobiotics because of its strategic anatomical function. Liver diseases represent a significant health problem due to their limited complications and treatment possibilities. The phytotherapeutic researches for the treatment of hepatic disorders generally use animal models for the induction of hepatotoxicity, and the hepatic damage promoted by the administration of carbon tetrachloride (CCl4) is one of the most accepted and widespread models. Several species of Baccharis are widely used in folk medicine, mainly in the form of infusions, to treat various disorders, such as liver and gastrointestinal problems. The BtHE presented high levels of polyphenols (0.152 g GAE/100 g DW), flavonoids (19.07 g CE/100 g DW) and tannins (20.165 g CE/100 g DW) and a high antioxidant capacity, mainly for lipophilic substrates (59.23% inhibition of linoleic acid peroxidation). The extract promoted a slight synthesis of collagen in the liver, in agreement with the control group, and CCl4 did not promote significant fibrosis. In the evaluation of oxidative stress in hepatic tissue, the extract protected the liver from lipoperoxidation (300 mg/kg) and carbonylation of proteins (300 and 600 mg/kg) (p <0.05). The extract also demonstrated a hepatoprotective effect by reducing the activity of the enzyme alanine aminotranferase in serum and no alteration of serum proteins. For the study of a possible antifibrotic effect, a better adaptation of the experimental animal model is necessary, because in this study it was not possible to detect the fibrotic effect of CCl4 and a possible antifibrotic effect of BtHE.